COMPARISON BETWEEN ORGANIC CHROMIUM AND ORGANIC ACIDS FOR REDUCING EXPERMINTALY INFECTED BROILER CHICKS BY SALMONELLA TYPHIMURIUM: Shahrazad A. Al-Shadeedi, Faris A. Al-Obaidi, Galib. A. AL-Kaisi ,and Zaynab Abdullzahra - Al-Shadeedi, Shahrazad A. (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to compare the effect of adding organic chromium (Biochrome) andorganic acids (Galli acids) for reducing experimentally infected broiler chicks by Salmonellatyphimurium . A total of 400 one day old broiler chicks were divided into four dietary groups whichwere: un-treated negative control (T1) , 044 ppb organic chromium / kg feed (T2) , 4.0 of organic acids/ kg feed (T3) and positive control (T4) . After one day of feeding T2 ,T3 and T4 chicks were oralexperimentally infected by S. typhimurium. Results have shown :Mortality of positive control broiler chicks were 70 % , added organic chromium and organic acidsreduced chicks mortality tto 10 % in each , also the results revealed that the addition of organic acidsand organic chromium reduced S. typhimurium in the intestine content and its recommended for use toprevention S. typhimurium infection in broiler chicks due to the improvement of health statusdepending on the increase of lymphocyte cells number and immunoglobulin concentration after 10 and21 days of experimentally infected , also the improvement in the live body weight and weight gain